Krajobraz przemian społecznych w małopolskiej gminie Michałowice w latach 1918–1945 - Chorązki, Marcin (Komunizm: System - Ludzie - Dokumentacja, 2023)
The aim of this article is to trace the social changes in the Michałowice commune near Cracow in the so-called ‘long duration’, from the end of the Poland’s Partitions (1918) to 1945. The author is interested not only in portraying selected opinions held by the local population, but above all in depicting the social and demographic changes from the fall of the partitioning powers, through the interwar period, to the end of World War II and the Communist takeover. The key is not only to show the losses, in the form of the disappearance from the social landscape of the three population groups present in this society, but also to emphasise how important this was for the local population. The author also wonders whether these changes really led to the impoverishment of the local population in any area. Perhaps they were expecting these changes, or they were not of significant importance. The analysis of the collected material allows us to conclude that the boundaries between the partitions during the years of captivity, and then historically within a single commune in the interwar period, remained in the collective memory. They were not erased by political, social or demographic changes, despite the social revolution brought about by the Communist authorities.